A haunted road atlas : sinister stops, dangerous destinations, and true crime tales - Schiefer, Christine; Schulz, Em (Andrews McMeel Publishing, 2022)
Pack up your Ouija board, wine bra, and squirt guns full of holy water ... we're going on a road trip! From the hit podcast And That's Why We Drink, this is your interactive travel guide to the hosts' favorite spooky and sinister sights. The world is a scary place ... and that's why we drink!